Environmental pressures to the water resources in the wider area of Roditsa, in Sperchios River Delta of Eastern Central Greece - Katsifa, M.; Koumantakis, I.; Stathopoulos, N.; Vasileiou, E. (Bulletin of the Geological Society of Greece, 2013)
The aim of this paper is to describe the ``pressures`` in the water environment, focusing in the water quality regime. The study area is located in the east – southeast of Lamia, southwest of the mountain Orthris, up to Maliakos gulf. The groundwater quality, regarding its irrigative use, ranges between good and moderate. The main sources of water deterioration are agricultural activities and sea intrusion near the coastline. Similar conditions are observed in the surface water of the area. Concerning the qualitative suitability of the water for irrigation, in the majority of the area’s surface water samples that were tested, there is a fluctuation between good and moderate. The hydrological data from the karstic springs were evaluated and several estimations were made, for describing their hydrodynamic regime. Certain proposals are suggested for the sustainable management of the water resources, concerning the proper use of the karstic springs and surface water, the reuse of sewage water, the exploitation of groundwater and a number of further actions that should be taken under consideration based on the European legislation